1993
DOI: 10.1042/cs0850525
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance of Stress: Sites and Mechanisms

Abstract: 1. Stress is associated with a severe, yet reversible, form of insulin resistance. The aim of this study was to quantify the kinetics of insulin action (sensitivity and responsiveness) on intermediary metabolism during post-surgical stress. 2. We studied nine patients 6-8 h after major uncomplicated surgery, and eight healthy subjects matched for age, weight, glucose tolerance and duration of fast. A three-step isoglycaemic insulin clamp was combined with indirect calorimetry, [6-3H]glucose infusion and the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 0 publications
4
28
1
2
Order By: Relevance
“…Thus, in deep forearm tissues the peak effect of insulin was to promote the uptake of 3 ymol min ' of glucose per each 10 ,umol min -' of oxygen regardless of blood flow. For comparison, in eight age-matched insulin sensitive subjects receiving an insulin infusion of the same duration and dose (28), the glucose to oxygen ratio in the forearm was 0.65±+0.23, i.e., more than twofold higher (P < 0.01) than in the present hypertensive subjects. The implication of these results is that the insulin resistance of essential hypertension is predominantly a cellular phenomenon rather than a restriction in insulin and glucose delivery to muscle tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in deep forearm tissues the peak effect of insulin was to promote the uptake of 3 ymol min ' of glucose per each 10 ,umol min -' of oxygen regardless of blood flow. For comparison, in eight age-matched insulin sensitive subjects receiving an insulin infusion of the same duration and dose (28), the glucose to oxygen ratio in the forearm was 0.65±+0.23, i.e., more than twofold higher (P < 0.01) than in the present hypertensive subjects. The implication of these results is that the insulin resistance of essential hypertension is predominantly a cellular phenomenon rather than a restriction in insulin and glucose delivery to muscle tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Například někteří autoři se domnívají, že schopnost oxidovat glukózu je u septických pacientů vyšší při porovnání se zdravými dobrovolníky (71), zatímco jiní tvrdí, že je nižší (72-74) nebo se nemění (66,75). Brandi dokumentoval, že celotělová oxidace glukózy probíhá preferenčně v játrech a jiných tkáních než svalových (76). Zároveň i na úrovni jednotlivých svalů a zastoupení typů svalových vláken se oxidace liší (77,78).…”
Section: Skořepa a Kol: úStřední Role Glukózy V Metabolismu A Výživěunclassified
“…As shown by studies in experimental animals and in man, post absorbtive glucose production (sustained by the liver and to a lesser extent by the kidneys [5]) is regulated by plasma glucose concentration itself [4] insulin and counterregulatory hormones (mainly glucagon and adrenaline) [6]. Case control studies have shown that in the postabsorptive state diabetic patients in poor metabolic control [2] and severely stressed people [7] have an increased rate of endogenous glucose output (EGO), which is almost invariably associated with a reduced plasma glucose clearance and, therefore, hyperglycaemia. Due to the technical difficulty of using tracers in large groups of subjects, the physiologic determinants, the normal values and the true degree of inter-individual variability of postabsorptive EGO have, however, not been determined.…”
Section: : 1266±1272]mentioning
confidence: 99%